Mobile Broadband Expansion Calls for More Spectrum or Base Stations - Analysis of the Value of Spectrum and the Role of Spectrum Aggregation - Jan Markendahl; Östen Mäkitalo; Bengt G. Mölleryd; Jan Werding (International Telecommunications Society (ITS), 2010)
The breakthrough for mobile broadband is taking the mobile communications industry into a new phase. The number of mobile broadband users in the world exceeds 400 million, and the share of the population in Western Europe with mobile broadband is around 10 per cent and over 15 percent in Austria and Sweden. This development has been propelled by the extensive diffusion of mobile modems (dongles) for laptops and smartphones given users ubiquitous access to mobile internet. Consequently, traffic volumes in the mobile networks have grown immensely, and the mobile data traffic surpassed the mobile voice traffic in the world by the end of 2009, and in for example Sweden, over 75 percent of the mobile traffic is data.
Keywords: 330